The Culture of Hospitality in Moldova and the United States - Dobrovolska, Anastasiia; Holtz, Rolf (Journal of International Students, 2013)
This tongue-in-cheek comparison between the unplanned visit and invasion by Mongolian-Tatarian tribes signifies at least two aspects of Moldovan hospitality. First, the treatment of guests in one’s home follows a cultural norm that prescribes not only the attitude toward visitors, but also the protocol of a host’s behavior. Moldovan rules of hospitality provide hosts with guidelines for proper comportment during a visit. Second, the adage suggests that guests can expect their host to adhere to a traditional standard of hospitable conduct. This helps to eliminate the uncertainty guests might experience in someone else’s home and alerts them to the efforts their host exerts on their behalf. In the United States, hospitality is also highly valued. However, norms for a host’s conduct are likely to range widely given the many cultures that shape American society.